“I was the ‘Energizer Bunny’ and now I’m the turtle’The effect of fatigue on the identity of people living with multiple sclerosis - Katharine Preissner; Lisa M. Baumgartner (Adult Education Research Conference, 2015)
Issues of identity among people with fatigue from multiple sclerosis were explored. Participants experienced changes in self-perception and struggled with not seeing themselves as busy and active as before MS. Some described a mourning process which led to resolution of a new identity. The findings have implications for health educators.
Keywords: Multiple Sclerosis; identity; fatigue